Implementation Of Expert Advisor Using Multi-Indicator Bollinger Bands And RSI Optimization With Adaptive Money Management On XAU/USD Pair: Exness Broker Account Case Study In Metatrader 5: Penelitian - Daniel Marco Hutabarat; Haikal Rahman; Dita Eka Pertiwi Sirait (Lembaga Penelitian dan Pengabdian Masyarakat, 2025)
Trading on the XAU/USD pair has high profit potential but is accompanied by significant volatility and emotional challenges for manual traders. This study aims to design, develop, and validate an Expert Advisor (EA) that can execute trading strategies automatically and profitably. The research method used is Research and Development (R&D) with a prototype model. The implemented strategy is a mean reversion strategy that integrates signals from the Bollinger Bands and Relative Strength Index (RSI) indicators, reinforced by an adaptive money management system to dynamically manage risk. The EA was developed on the MetaTrader 5 platform and tested through three main stages: backtesting on historical data, parameter optimization using the Fast Genetic Based Algorithm, and real-time testing for one month on an Exness broker demo account. The research results show that the optimization process successfully transformed the EA's performance from unprofitable to profitable. In real-time testing, both time frames tested showed positive results. The H1 time frame proved more robust, generating a net profit of 546.11 from three transactions and a Profit Factor of 3.92. Meanwhile, the H4 time frame demonstrated superior precision with a Win Rate of 100% and a Max Drawdown of 1.41% from a single transaction. This study concludes that the developed Expert Advisor is a valid and potentially profitable system for XAU/USD trading, with the H1 time frame offering more proven performance for practical application.